2019
DOI: 10.32098/mltj.02.2019.02
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical characteristics of Vietnamese adult hip joint: a multiplanar reconstruction computer tomographic study

Abstract: Background. The present study evaluated some anatomical characteristics of the acetabulum and proximal femur in the hips of adult asymptomatic Vietnamese individuals. Methods. We used 32 slice computed tomographic system with a multiplanar reconstruction (MPR CT) protocol to evaluate several parameters of the acetabulum and proximal femur, including Acetabular diameter (ADi), Acetabular depth (ADe), Acetabular ratio (AR, calculated by (ADe/ADi) x100), Acetabular inclination angle (AI), Acetabular anteversion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In our study, the average size of the acetabulum was 50.22 ± 3.5 mm, which is similar to the study by Tran Trung Dung (2019) of 50 ± 2.9 mm, both on a group of mature Vietnamese individuals. 4 The depth of the acetabulum and acetabular depth ratio in our study were 18 Baharuddin's study (2018) 6 of Malaysians, Paul's study 7 of Indians, and Arsic's study 8 of Serbians, in which no statistically significant difference was found in acetabular depth and index. The average size of the femoral head in our study was 43.54 ± 3.68 mm, which was not statistically different from Tran Trung Dung's study (2019).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In our study, the average size of the acetabulum was 50.22 ± 3.5 mm, which is similar to the study by Tran Trung Dung (2019) of 50 ± 2.9 mm, both on a group of mature Vietnamese individuals. 4 The depth of the acetabulum and acetabular depth ratio in our study were 18 Baharuddin's study (2018) 6 of Malaysians, Paul's study 7 of Indians, and Arsic's study 8 of Serbians, in which no statistically significant difference was found in acetabular depth and index. The average size of the femoral head in our study was 43.54 ± 3.68 mm, which was not statistically different from Tran Trung Dung's study (2019).…”
Section: Discussionmentioning
confidence: 44%
“…The average size of the femoral head in our study was 43.54 ± 3.68 mm, which was not statistically different from Tran Trung Dung's study (2019). 4 Regarding the differences in this index between different ethnicities and genders, Edward reported in 2020 that there were statistically significant differences between ethnic groups, especially between the Chinese and white European, white American, and African American populations. 2,[9][10][11] In terms of the orientation angles of the acetabulum in space, we compared our results with those of other authors in the literature (Table 5).…”
Section: Discussionmentioning
confidence: 99%